Political Strategy of Legislative Candidates Moch. Irfan in the 2019 Election from the National Democratic Party in Dapil II Tegal Regency - M. Zimamul Khaq (Tinta Emas Institute, 2023)
This research reveals Moch's political strategy. Irfan in the 2019 Election. First, he maximized his power by focusing his campaign team in his base village, running an economical campaign, engaging youth, getting support from religious leaders (NU) from the PKB/PPP Party, avoiding competition within the extended family, promoting the slogan